Text â Shape Defamiliarization in contemporary Arabic Poetry (servey and Review) - Ali Akbar Mohseni; Reza Kiani (دراسات في اللغة العربيّة وآدابها)
Contemporary poets have employed all their literary devices to add creativity to their work . defamilian zation in text shape is one such device to break away from familiar writing conventions and create new implication. This device is also considered in modern stylistic studies. In this technique the author tries to create new images and can achieve the goal in different ways: 1) disrupting the physical form of the words, 2) using unfamiliar arrangements and spacing of words in the poetic texts, 3) mixing the text with words and phrases from other languages, 4) employing different shapes and graphic devices in the body of the poems. This study shows that modern poets mix linguistic content with visual effects to create particular messages and implications. However, this technique sometimes does not add to the beauty of the poem but detract from its value making it banal.